Verticillium dahliae VdPBP1 Transcription Factor Is Required for Hyphal Growth, Virulence, and Microsclerotia Formation - Huong Thi Nguyen; Thanh Thi Duong; Vu Xuan Nguyen; Tien-Dung Nguyen; Thuc Tri Bui; Dung Thuy Nguyen Pham (Microorganisms, 2024)
Verticillium dahliae, a fungal pathogen that affects more than 200 plant species, including tomatoes, requires specific proteins for its early steps in plant infection. One such crucial protein, VdPBP1, exhibits high expression in the presence of tomato roots. Its 313-amino acid C-terminal section restores adhesion in nonadhesive Saccharomyces cerevisiae strains. To uncover its role, we employed a combination of bioinformatics, genetics, and morphological analyses. Our findings underscore the importance of VdPBP1 in fungal growth and pathogenesis. Bioinformatic analysis revealed that the VdPBP1 gene consists of four exons and three introns, encoding a 952-codon reading frame. The protein features a 9aaTAD domain, LsmAD, and PAB1 DNA-binding sites, as well as potential nuclear localization and transmembrane helix signals. Notably, the deletion of a 1.1 kb fragment at the gene’s third end impedes microsclerotia formation and reduces pathogenicity. Mutants exhibit reduced growth and slower aerial mycelial development compared to the wild type. The VdPBP1 deletion strain does not induce disease symptoms in tomato plants. Furthermore, VdPBP1 deletion correlates with downregulated microsclerotia formation-related genes, and promoter analysis reveals regulatory elements, including sites for Rfx1, Mig1, and Ste12 proteins. Understanding the regulation and target genes of VdPBP1 holds promise for managing Verticillium wilt disease and related fungal pathogens.